Wheat Cost-Return Budget in Southeast Kansas - O'Brien, Daniel M.; Shoup, Douglas; Dhuyvetter, Kevin C. (My University, 2014)
This publication outlines the expected costs and returns for wheat in southeast Kansas.
MF992_2014_02
Keywords: MF992; Economics; Crops; MF